Risk Management for 4-H Youth Development Work: Special Events and Activities - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS)
4H10.3, a 4-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It describes ways to prepare for risks when 4-H has special events like fairs, conferences, and overnight trips. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.